THE DEVELOPMENT OF QUALITY OF LIFE INSTRUMENT - Mohd Zanuddin, Nur Hazwani; Ahmad, Muhamad Firdaus; Adnan, Afnan Aizzat; Zakaria, Fazlinawati (Journal of Human Capital Development (JHCD), 2019)
The purpose of this research is to develop an instrument to measure the quality of life based on constructs or factors proposed within academic and non-academic institutions. Two different institutions were selected in the study which are Kolej Poly-Tech MARA Alor Setar (KPTM) and Muda Agriculture Development Authority (MADA). Literature review has been done and a conclusion on the key components (construct) of quality of life instrument are general health and functional status, socio-economic status, life satisfaction and self-esteem. Content validity is done with expert validation to improve the items that has been develop. Face validity is achieved by focus group in two different institutions to gain the feedback and opinion regarding the questionnaire. For pilot test, questionnaires were distributed to 50 respondents for each institution respectively. Then, the pilot test results were used to conduct reliability test – Cronbach’s Alpha Coefficient and Exploratory Factor Analysis. The finding show that the reliability testing has achieved a satisfactory level by using EDA in depth understanding is obtained and cross checked with Cronbach’s Alpha and EFA value. Concerning to the current findings in academic and nonacademic area, the 4 constructs of Quality of Life would be maintained without the changing or reducing the total factors that emerge from the analysis. Keywords: quality of life, content validity, face validity, factor analysis